Structure-function relationships of the liver and muscle isoforms of carnitine palmitoyltransferase I. (May 2001) - Zammit, V. A.; Price, N. T.; Fraser, F.; Jackson, V. N.
Abstract : Elucidation of the membrane topology of carnitine palmitoyltransferase (CPT) I showed that the extreme N-terminus is involved in determining the sensitivity of the liver (L) isoform to malonyl-CoA and suggested that interaction between the two cytosolic segments of the CPT I molecule determines the kinetic characteristics of the enzyme. Work with chimaeric liver/muscle-isoform (L/M) proteins constructed from all six possible combinations of three domains [N-terminus plus transmembrane domain 1 (TM1), loop plus TM2 and C-domain] expressed in Pichia pastoris showed that the precise N-C and TM1-TM2 pairings determine the overall kinetic parameters of the protein. Discrete short sequences within the respective N-terminal regions have negative or positive effects on malonyl-CoA sensitivity (L-isoform) or the K m for carnitine (M-isoform) in the full-length proteins, thus imparting to them their distinctive kinetic characteristics. Interactions within N-terminal domains also seem to be important in the targeting of the protein to microsomes in the P. pastoris expression system.